Effect of accelerated corneal crosslinking on ocular response analyzer waveform-derived parameters in progressive keratoconus - Uzel,Mehmet Murat (2019)
ABSTRACT Purpose: To evaluate the effect of accelerated corneal crosslinking on corneal biomechanics with an ocular response analyzer in patients with progressive keratoconus. Methods: In this retrospective study, 50 eyes of 45 patients with progressive keratoconus who underwent accelerated corneal crosslinking were evaluated with ocular response analyzer waveform parameters before and one year after corneal crosslinking. Paired two-tailed Student’s t-test was performed to compare the parameters before vs. after corneal crosslinking. Results: Mean patient age was 17.6 ± 3.6 (range 9-25) years. A significant increase was observed in p1 area, p2 area, h2, and dive2 values. No significant difference in corneal hysteresis, corneal resistance factor, or other waveform-derived parameters was observed at one year postoperatively. Conclusion: For estimating the effect of accelerated corneal crosslinking on corneal biomechanics, parameters such as p1 area, p2 area, h2, and dive2 are more sensitive than corneal hysteresis and corneal resistance factor. These results may help us to find out which corneal crosslinking method is most effective for stiffening the cornea.